ANALISIS STRUKTUR MODAL DAN NILAI PERUSAHAAN YANG DIUKUR DENGAN TOBINS’Q - Lailatul Amanah (EKUITAS (Jurnal Ekonomi dan Keuangan), 2007)
The objective of this study is to analize whether the increasing leverage followed by increasing values of the firm, and examine differences stock return before and after laverage increase. This study develops Kusumawati’s reseach (2005) about optimal capital structure, that analize three stocks in knowing the changes of leverage and of value of the firm. Sample of this reseach are companies which increase leverage  without changing the number of stock.The result of this study shows that the increasing leverage followed by the increasing value of the firm. This is consistent with the previus study (Suranta and Mahfoedz, 2003). But the test of stock return differencies before and after the leverage increase does not show a significant result. This result is not consistent with The Masulis Study (1980). He found that a company which changes stocks to loan will increase its stock return up to 6,6%.